2019
DOI: 10.30799/jnst.278.19050505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cadmium Oxide Nanoparticles by Electrochemical Method: Its Photodegradative Effects on Carboxylic Acids and Antibacterial Behaviours

Abstract: Cadmium oxide (CdO) nanomaterial has been synthesized by electrochemical method which is simple and inexpensive method. The synthesized cadmium oxide nanomaterial was used as a catalyst for the photocatalytic degradation of acetic acid, formic acid and oxalic acids under varies experimental conditions by volumetric method. The synthesized nanomaterials were characterized by various techniques such as UV-Visible spectroscopy, SEM-EDAX, FT-IR spectrum and X-ray diffraction studies. The UV-VIS spectroscopy study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Abbas et.al described the sonochemical mediated synthesis of Cd(OH) 2 , CdO and Cd(OH) 2 /Ag core/satellite nanorods, & their physical and chemical properties were investigated[21]. Kumar et.al reported that the prepared CdO NPs utilized for nanocatalysts to degrade acetic, formic and oxalic as well as show excellent antibacterial activity against Escherichia coli and Bacillus subtilis[31]. Mirzaei et.al reported that the carrageenan-assisted approach synthesized CdO and Cd(OH) 2 NPs exhibit different morphologies.…”
mentioning
confidence: 99%
“…Abbas et.al described the sonochemical mediated synthesis of Cd(OH) 2 , CdO and Cd(OH) 2 /Ag core/satellite nanorods, & their physical and chemical properties were investigated[21]. Kumar et.al reported that the prepared CdO NPs utilized for nanocatalysts to degrade acetic, formic and oxalic as well as show excellent antibacterial activity against Escherichia coli and Bacillus subtilis[31]. Mirzaei et.al reported that the carrageenan-assisted approach synthesized CdO and Cd(OH) 2 NPs exhibit different morphologies.…”
mentioning
confidence: 99%